Work Statisfaction And Work Performance: How Project Managers In Malaysia Perceive It? - Jaafar, Mastura; T, Ramayah; Zainal, Zainurin (2006)
The performance of project managers is very important to ensure the success of any construction project. In spite of the complexity of construction projects (which involves different design, material, consultant, environment and so on), managers also have to ensure that the project can meet the client's satisfaction.